Evaluation of optimum measurement device, time analysis and workload of performing quality assurance tasks by physicists on medical linear accelerator - Intang, Wilfred (2021)
The implementation of the Radiotherapy Quality Assurance Program (QAP) safety standard by Malaysia Ministry of Health (KKM) is to ensure safe and efficacious application of ionizing radiation and minimize error in the treatment of cancer. With the new advance treatment technique and with the increasing number of cancer patients, the QAP implementation is crucially important. But this also demands a lot of physicist’s working time. Lack of physicist and quality control (qc) device were among the problem encountered by most of the radiotherapy services in this country as reported by NHEWS Report (2010) and this has become a major issue for the QAP system to be in place. Therefore, it is particularly important to optimize whatever resources available. This study has made some recommendations regarding the qc tools suitably optimize for specific tasks. EPID is the best option for the quality control (qc) device. It had recorded flatness standard deviation of 0.77 percent, while the measured standard deviation of symmetry was 0.33 percent. EPID also provide sufficiently accurate measurement for the light and radiation field congruent test. With task timing, the Total Man Hours per linac for the machine qc was 62 Man-Hours per year or 5.2 Man-Hours per month. For a typical radiotherapy clinic, this translates to approximately five physicists per linac machine. The patient specific qc task had recorded approximately 42 Man-Hours per year of physicist’s working time, higher compared the other qc tasks. This is equivalent to 3.5 Man-Hours per month or approximately four physicists that required to perform this task. Both calculation in the WISN method and Man-Hours method had concluded that nine physicists are required in Sabah Women and Children Hospital (HWKKS), while the actual number of physicists working there at the time of this study was six. It means shortage of three physicists or equivalent to 0.67 by ratio calculation of the WISN. At the time of this research, there are limited or probably no evaluation study on qc device as well as the timing qc task study with respect to the implementation of the QAP radiotherapy standard in this country. By evaluate these QAP requirements, the gap between optimal and actual use of resources was identified. Different approach of methods such as using the Failure Modes and Effects Analysis (FMEA) in the qc program was recommended. The research was conducted on four medical linac in two hospitals.